2000
DOI: 10.1007/pl00011713
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis cystica polyposa associated with a gastric stump carcinoma, with special reference to cell kinetics and p53 gene aberrations

Abstract: We report a case of gastritis cystica polyposa (GCP) that developed in association with a small stump carcinoma. The patient had had distal gastrectomy for peptic ulcer 33 years prior to the present illness. Total gastrectomy was carried out for the stump carcinoma of the remnant stomach, followed by Roux-en-Y anastomosis. Histological examination revealed that the cancer was associated with a GCP lesion in its neighborhood. The resected stomach was subjected to a cell kinetics study and p53 gene analysis, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…22,23 High cell proliferation activity in the epithelium of GCP has been reported. 24,25 The reflux of bile and pancreatic juice is considered to cause regenerative atypia and cell proliferation in epithelial cells, resulting in the formation of GCP. 25,26 This is in contrast to observations in the non-remnant stomach, i.e., marked atrophy and moderate-to-marked lymphocytic infiltration are characteristic of EBV-associated GC.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 High cell proliferation activity in the epithelium of GCP has been reported. 24,25 The reflux of bile and pancreatic juice is considered to cause regenerative atypia and cell proliferation in epithelial cells, resulting in the formation of GCP. 25,26 This is in contrast to observations in the non-remnant stomach, i.e., marked atrophy and moderate-to-marked lymphocytic infiltration are characteristic of EBV-associated GC.…”
Section: Discussionmentioning
confidence: 99%
“…The solid portion was relatively obvious (mucosal polypoid hyperplasia) and was often accompanied by fine pointlike cystic changes internally [4][5][6][7][8][9][10]12]. However, this cohort only had one case similar to the reports in the literature, whereas the remaining cases were primarily dominated by the cystic component, with thick mucosal hyperplasia on the surface.…”
Section: Discussionmentioning
confidence: 83%
“…Pathogenesis of GCP is still elusive. It is reported that inflammatory infiltration and intestinal reflux may be the primary pathogenetic mechanisms [7]. However, only a few reports have presented imaging findings of primary GCP that was not associated with a history of gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Koga et al described that there were 4 cases of GCP (9.5%) in their 42 patients who had once undergone gastrojejunostomy and received further surgery on account of various reasons (9). In Japan, there are many reports describing the association of GCP with early or small cancerous lesions in the remnant stomach (11,12). Thus GCP has been proposed to be a possible precancerous lesion itself (13).…”
Section: Discussionmentioning
confidence: 99%